Pengajian Remaja Dan Kontribusinya Dalam Pembentukan Akhlak Generasi Muda Di Bulak Setro Surabaya - Achmad Nawawi (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Spiritual spirits is a non-formal education activities conducted in a place of worship in an Islamic society as a place to deepen and examine the knowledge of religion, whether morals, worship, or muamalah. While the material is taught in spiritually spirited teen Bulak Setro is more to morality material that aims to shape morals on the younger generation. While teenagers spiritual spirits efforts conducted by teenagers Bulak Setro in forming the morality of the young generation that is by providing education, pedagogy, habituation, and exemplary to the congregation (members) sprinkling the spiritual. This research uses qualitative approach, with observation research technique, documentation, and interview. As for data analysis in this study using qualitative analysis. The credible test uses triangulation or checking data from multiple sources in various ways and times. The study of adolescents has a huge contribution in the formation of morality of the younger generation in the future, the region prepares its generation with positive things so it becomes a habit for teenagers to attend a recitation, as an exercise to cultivate a sense of responsibility by becoming a tutor, without losing their adolescence, because people still give them the freedom to play and hang out like any other teenager.